Implementation of the DSM-5 and ICD-11 Dimensional Models of Maladaptive Personality Traits Into Pre-bariatric Assessment - Riegel, Karel D.; Konecna, Judita; Matoulek, Martin; Rosova, Livia (Frontiers in Psychology, 2022)
Background: Personality pathology does not have to be a contraindication to a bariatric surgery if a proper pre-surgical assessment is done. Indicating subgroups of patients with their specific needs could help tailor interventions and improve surgical treatment outcomes. Objectives: Using the dimensional Alternative DSM-5 model for personality disorders (AMPD) to detect subgroups of patients with obesity based on a specific constellation of maladaptive personality traits (PTs) and the level of overall impairment in personality functioning. Methods: 272 consecutively consented patients who underwent a standard pre-surgical psychological assessment. The majority were women (58.0%), age range was 22-79 years (M = 48.06, SD = 10.70). Patients’ mean body mass index was 43.95 kg/m2. All participants were administered the Personality Inventory for DSM-5 (PID-5) from which Level of Personality Functioning Scale-Self Report (LPFS-SR) scores were gained using the "crosswalk" for common metric for self-reported severity of personality disorder. The k-means clustering method was used to define specific subgroups of patients with obesity. Results: The cluster analysis detected specific groups in the sample of patients with obesity, which differed quantitatively from the samples of non-clinical respondents and psychiatric patients. A vast majority of patients with obesity showed above-average values in most of the PID-5 facets compared to the US representative general community sample. In 2 out of the 3 clusters defined, patients demonstrated moderate (> M + 1.5*SD) to severe (> M + 2.0*SD) personality psychopathology within the obsessive-compulsive and borderline spectrum of maladaptive PTs according to PID-5, which has been to some extent supported by the mild (M = 1.63, SD = .22) to moderate (M = 2.18, SD = .27) level of overall impairment in personality functioning according to LPFS-SR. Moreover, higher levels of psychopathology prove to be associated with higher age and use of psychiatric medication. Conclusions: The dimensional AMPD model of PTs is a reliable procedure for defining specific “characters” of patients in a pre-bariatric setting. As such, it helps to identify subgroups of patients with obesity whose long-term therapy success is likely to be impeded given their personality structure. Implications for clinical practice and further research are discussed.